ANALYSIS OF THE EFFECTIVENESS OF THE SPECIAL ALLOCATION FUND PERSPECTIVE IN REGIONAL DEVELOPMENT IN SIMALUNGUN REGENCY - Tuahman Sipayung; Joni Wilson Sitopu; Yusmaita Fafriani Saragih (SEAN Institute, 2022)
The study's objective is to evaluate and clarify how the Special Allocation Fund has improved the development of the region's road infrastructure. This study employed secondary data that covered the years 2011 through 2020, and it used the Mixed Method Analysis data analysis technique, which combines qualitative descriptive analysis and quantitative descriptive analysis. The object under study is the result of the Simalungun Regency Government Financial Report on the Special Allocation Fund for Road Infrastructure in Simalungun Regency. The study's findings show that the Special Allocation Fund for Road Infrastructure is Quite Effective in Increasing Road Infrastructure Development in Simalungun Regency because the Special Allocation Fund is the main source of Road Infrastructure Development in Simalungun Regency. In order to achieve quality and sustainable economic growth, the government should give special attention to the development of road infrastructure. Policies that can support road infrastructure development are required to help increase economic growth that can be felt by the community.